The Trace of Evidence Based Medicine in Avicenna\'s Approaches - L Kashani; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2016)
Many factors underlie the growing popularity of herbal treatments for a variety of chronic conditions. Interestingly, people who use alternative therapies are not necessarily uninformed. If anything, they are more "culturally creative" (i.e., comfortable with cultural changes) and more highly educated. Many people using herbal medicines find the health care alternatives are more congruent with their own values, beliefs and philosophical orientations toward health and life. Similarly, it seems likely that many people feel that herbal medicines are empowering by allowing them to treat themselves without seeing a physician. (This same attitude may be behind the growing popularity of patient-initiated diagnostic scanning procedures such as whole body scans). The danger is that, many people believe that herbal medicines have no toxicity problems or even side effects. In addition, they are not aware of many possible interactions of herbal medicine with concurrent prescribed medications. In this review we focus on Avicennachr('39')s evidence based medicine approaches in herbal medicine.